Results of a community-based screening programme for chronic kidney disease and associated risk factors, (obesity, diabetes and hypertension) in a Samoan cohort. Issue 4 (8th April 2022) - Tafuna'i, Malama; Turner, Robin; Matalavea, Ben; Voss, David; Hazelman, Lose; Richards, Rosalina; Walker, Robert
Abstract : Objectives: In 2019, under the World Kidney Day theme of 'Kidney health for everyone everywhere', the National Kidney Foundation of Samoa undertook an extensive community screening campaign to detect the estimated prevalence of chronic kidney disease (CKD) and its associated risk factors in the community. Setting: Fifteen screening sites, with 11 urban and rural sites on the main island of Upolu, and 4 in different rural areas on the island of Savaii. Participants: All participants were self-referrals to the various screening sites. In total, 1163 Samoans were screened, with similar numbers from both urban and rural areas and similar numbers of female and male. Screening activities: All participants were screened for CKD using point of care serum creatinine determinations, with calculation of estimated glomerular filtration rate using the CKD-EPI formula and dipstix urinalysis. A standardised screening survey was used to capture demographic and medical history with associated risk factors of obesity, diabetes, using point of care determination of HbA1c and hypertension. Logistic regression was used to investigate the association of CKD with risk factors. Results: In total, 1163 people were screened for CKD within the month of March 2019. The prevalance of CKD (grades 1–5) was 44.5% (95% CI 41.6% to 47.4) with individual grade prevalence CKD 1: 3.7%, CKD 2: 6.1%, CKD 3: 30.7%, CKD 4: 2.9% and CKD 5: 1.0%. The prevalence of obesity (body mass index ≥32), diabetes and hypertension was 66.3%, 30.8% and 54.3%, respectively. Conclusions: This is the first paper to report the estimated prevalence of CKD in Samoa or any other Pacific Island nation. It reveals an urgent need for further studies on the epidemiology of CKD in Samoa, to develop country-specific prevention strategies to mitigate this growing burden and prevent subsequent CKD associated complications including development of kidney failure and premature death.